ANALISIS PENGGUNAAN HUTANG TERHADAP PROFITABILITAS PT WAHANA ABADI RUKUN AGUNG SEJAHTERA BANDAR LAMPUNG - Ardansyah -; Yohanes Davit Widarto (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
The purpose of this research was to determine the effect of the use of debt to the profitabilityof the company PT. Wahana AbadiRukun AgungSejahtera Bandar Lampung. The data used is afinancial data company balance sheet and income statement in 2008 until 2012, and then processedinto more specific data to make it easier to analyze. The analytical tool used in this research is asimple linear regression analysis model, used to see the connection between the use of debt as aindependent variable (X) with the profitability of the company as the dependent variable (Y), whichhypothesis that the use of debt has a positive effect on the profitability of the company.The regression equation obtained was Y = -10.806 + 0.166X, this shows that the positiveinfluence between the use of debt to the company's profitability. Based on hypothesis testing with thet-test obtained 17.107 as t count and 2,776 as t table. This means that Ho was reject and Ha wasaccept because -t table > -t count, t count>t table so it can be concluded that the effect of significantlybetween the use of debt to profitability